Implementing security in IoT systems via blockchain. (1st November 2022) - Parcha, Anurag; Mishra, Sanjana; Bist, Aditya; Agarwal, Reema; Gupta, Sagar; Sharma, Saahil; Sathyaraj, R.
Today, IoT systems have become prominent, especially in the fields of healthcare, agriculture, and manufacturing. IoT systems encompass numerous devices that become targets for attacks and exploitation, thereby making these systems prone to security vulnerabilities. While IoT has become a widespread technology by virtue of its scalability, dependability, and ease of access, its shortcomings should also be addressed. Currently, client-server model of networking is employed in IoT devices which use a single gateway for transferring data and connecting through a cloud server. This model demands a high cost for cloud maintenance and network equipment. Furthermore, a single gateway is not secure as one failed node can compromise the entire network. To improve security, we propose the inclusion of blockchain technology; a distributed ledger where data is stored across several nodes, thereby eliminating single point failure. This project proposes the benefits of blockchain technology in conjunction with security of IoT systems.